Effect of various temperatures and strain-rates combinations on the thermomechanical behavior of 42CrMo steel - Abdul-Latif, A.; Abed, F.; Oucif, Ch.; Voyiadjis, G.Z. (Archives of Mechanics, 2022)
This paper investigates experimentally the thermomechanical response of 42CrMo steel under several combinations of temperatures and strain-rate. To characterize the flow stress of this highstrength 42CrMo steel, two distinct test configurations were utilized. The first consisted of conventional uniaxial tensile tests conducted at room and elevated temperatures of 523°K, 723°K and 923°K and three quasi-static strain-rates at 0.0015 s-1, 0.015 s-1, and 0.15 s-1. The second test configuration was carried out under dynamic compression using a drop mass bench at room temperature with three different dynamic strain-rates of 300 s-1, 400 s-1, and 500 s-1. Particular attention was paid to key features such as work-hardening (WH), grain size, dynamic strain aging (DSA), formation of microcavities, and their coupling with the influence of temperature/strain-rate combination. The dependence of 42CrMo steels’ flow stress on the quasi-static strain-rate at room temperature was almost insignificant. However, the strain-rate sensitivity increased with increasing temperatures. At high temperatures, different factors contributed to modifying the alloy microstructure which has a significant impact on the alloy’s mechanical properties. Quantification of the micro-cracks density and fractured specimens’ voids was established using scanning electron microscopy (SEM) images. The Voyiadjis–Abed (VA) constitutive model was utilized in describing the flow stress of 42CrMo steels and implemented in the ABAQUS software to develop a robust finite element model capable of accurately simulating variant structural responses of 42CrMo steel alloy.